The Effects of Topical Sildenafil on Wound Healing in Rat: Attenuation of thermal hyperalgesia in diabetes by Thespesia populnea - Akram Jamshidzadeh; Negar Azarpira (Iranian Journal of Pharmaceutical Sciences, 2011)
Nitric oxide (NO) is an important molecule synthesized during wound repair. Studies have reported the use of NO donors on cutaneous wound repair, but their effects in different phases of healing are not elucidated. The aim of this work was to investigate the effects of topical sildenafil on wounds in rats. Sildenafil (25 mg) was topically applied once daily on wound in treatment groups. On days, 7, 14 and 21 of lesion, five animals in each group were randomly selected and sacrificed and histological properties were evaluated. Our results showed the wound area contracted to 15% of the original size by day 7 post-wounding in treated group. Whereas control rats showed significantly delayed wound healing. The wound area contracted to 26% of the original size by day 14 post-wounding and to 46% by day 21 post-wounding. Also sildenafil cream caused more fibroblast and macrophage migration, increased vascularization, collagen regeneration, and epithelialization. This study indicates that sildenafil cream augments the wound healing process and may be of clinical benefit.